2008
DOI: 10.1029/2007ja012628
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of magnetospheric electric fields to the equator during a geomagnetic storm

Abstract: [1] Penetration of the magnetospheric electric field to the equatorial ionosphere was examined for the geomagnetic storm on 6 November 2001, by analyzing the difference in magnitude of the geomagnetic storm recorded at the dayside geomagnetic equator, Yap (À0.3°GML) and low latitude, Okinawa (14.47°GML). The penetrated electric field caused the DP2 currents at the equator, i.e., eastward currents during the main phase of the storm, while the overshielding currents, i.e., westward currents dominated during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
236
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(249 citation statements)
references
References 46 publications
12
236
0
1
Order By: Relevance
“…During geomagnetically active periods, a counter electrojet is sometimes caused by the penetration of the polar-region electric field to equatorial latitudes (Rastogi and Patel 1975;Rastogi 1977Rastogi , 1997Kikuchi et al 2003Kikuchi et al , 2008. Besides, storm-time thermospheric winds tend to drive a westward electric field in the dayside equatorial region through the mechanism known as disturbance dynamo (Blanc and Richmond 1980;Fuller-Rowell et al 2002).…”
Section: Counter Electrojetmentioning
confidence: 99%
See 1 more Smart Citation
“…During geomagnetically active periods, a counter electrojet is sometimes caused by the penetration of the polar-region electric field to equatorial latitudes (Rastogi and Patel 1975;Rastogi 1977Rastogi , 1997Kikuchi et al 2003Kikuchi et al , 2008. Besides, storm-time thermospheric winds tend to drive a westward electric field in the dayside equatorial region through the mechanism known as disturbance dynamo (Blanc and Richmond 1980;Fuller-Rowell et al 2002).…”
Section: Counter Electrojetmentioning
confidence: 99%
“…Rastogi (1977), analyzing the difference in H at Huancayo (12.0°S, 75.3°W) and Fuquene (5.4°, 73.7°), recognized the occurrence of the counter electrojet during geomagnetic storms. Later, Kikuchi et al (2003Kikuchi et al ( , 2008 demonstrated how the penetration of high-latitude electric fields to lower latitudes can cause an enhancement and reduction (or reversal) in the equatorial electrojet. High-latitude electric fields penetrate to lower latitudes, most evidently when the magnetospheric convection suddenly increases or decreases.…”
Section: Storm Effectmentioning
confidence: 99%
“…As described by Abdu (1997;see also Buonsanto, 1999) major modifications in the equatorial ionosphere-thermosphere system during magnetospheric disturbances are produced by (a) prompt equatorward penetration of magnetospheric/high latitude electric fields (see also Senior and Blanc, 1984;Spiro et al, 1988), and (b) disturbance dynamo driven by enhanced global thermospheric circulation resulting from energy input at high latitude (see also Blanc and Richmond, 1980). Recently, Kikuchi et al (2008) and Veenadhari et al (2010) have investigated penetration of magnetospheric electric fields to the equator during magnetic disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…[4] The overshielding scenario can successfully explain some observations in space [e.g., Goldstein et al, 2002Goldstein et al, , 2003] and on the ground [e.g., Kikuchi et al, 2000Kikuchi et al, , 2008. However, the physics behind overshielding still require more extensive study.…”
Section: Introductionmentioning
confidence: 99%